(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Psoriasis is a chronic inflammatory skin disorder that has been increasingly associated with cognitive dysfunction. However, the prevalence of mild cognitive impairment (MCI) in psoriasis patients remains underexplored. This study aims to assess the presence of MCI in individuals with psoriasis using the Montreal Cognitive Assessment (MoCA) and examine its correlation with disease severity. Objectives: To evaluate the presence of mild cognitive impairment in patients with psoriasis and compare it with healthy controls using the Montreal Cognitive Assessment (MoCA) scale. Methods: A cross-sectional study was conducted on 50 patients diagnosed with psoriasis and 50 age- and sex-matched healthy controls. Cognitive function was evaluated using the Montreal Cognitive Assessment (MoCA), with a cutoff score of <26 indicating mild cognitive impairment (MCI). Disease severity in psoriasis patients was assessed using the Psoriasis Area and Severity Index (PASI). Statistical analyses, including Pearson’s correlation, Chi-square tests, and multiple regression models, were performed to determine the association between psoriasis severity and cognitive impairment. Results: The mean MoCA score was 24.31 ± 3.1 in the psoriasis group and 26.8 ± 2.5 in the control group (p value 0.002). Statistically significant differences were observed in the visuospatial abilities, executive functioning, and orientation domains. Conclusion: This study highlights a high prevalence of mild cognitive impairment in psoriasis patients, with disease severity being a key contributing factor. These findings emphasize the importance of cognitive screening using MoCA in psoriasis management. Further research is warranted to explore the underlying mechanisms and potential interventions for cognitive impairment in psoriasis.